Increased fat mass and obesity risk after elexacaftor–tezacaftor–ivacaftor therapy in young adults with cystic fibrosis - Merino Sánchez-Cañete, Ana; López Cárdenes, Concepción Marina; Vicente Santamaría, Saioa; Gutiérrez Martínez, José Ramón; Suárez González, Marta; Álvarez Merino, María; González Jiménez, David (Frontiers in Nutrition, 2024)
We wish to submit an original research article entitled "Increased fat mass and obesity risk after elexacaftor/tezacaftor /ivacaftor therapy in young adults with cystic fibrosis" for consideration by Frontiers in Nutrition We confirm that this work is original and has not been published elsewhere, nor is it currently under consideration for publication elsewhere. In this paper, we show body composition behavior of patients in the first months in treatment with Elexacaftor/Tezacaftor/Ivacaftor using bioelectrical impedance analysis. This is significant because the best of our knowledge, there are currently no studies using bioelectrical impedance analysis to assess body composition in PwCF on Elexacaftor/Tezacaftor/Ivacaftor. We believe that this manuscript is appropriate for publication by Frontiers in Nutrition because it reflects a change in the nutritional management of cystic fibrosis patients in line with the changes in body composition observed in our study. We have no conflicts of interest to disclose.